Именувањето на болестите во македонските средновековни текстови (Philological Studies, 2019)
The medical lexis confirmed in Macedonian medieval texts is indicative of the repertoire and the semantic contents of the lexemes. Besides lexemes for naming the specific diseases, there is also a descriptive way of expressing certain conditions. The alternative medicine arises great interest through fortune tales, prayers etc., i.e. the traditional way of treating diseases based on old folk customs and beliefs. The connection between the lexis of the Church-Slavic language and of the contemporary Macedonian language, i.e. Macedonian dialects, confirms the unity of the lexical system from a historical aspect. On the basis of the presented material, it can be perceived that the largest part of the lexis from the area of history of medicine is of Slavic origin (bol5nie, rana, prokaza), and part are Greek loanwords (ikter7, lepra, panoukla) or Turkish loanwords (ma3s7l7, damla, il5=7, safra, dalak7, mehlem7, mad'oun7). The wide spectrum of lexemes from this area can be reviewed through synonymic relations, for example: b5l6mo 9na o=i©0 - pavlaka - perde, bol5zn6 - bol5nie - bolest6 - ned4g7, b5d6n7 - malomo]69n70 - hrom7, vr5d7 - rana - jazva, 'l7tina - 'l7t5nica - 'l7taja bol5zn6 - ikter7, kr7tor7yja - gangrena - m7nih7, prokaza - proka'enie - lepra, stoud7 - nastoud7 - nastin6ka - lad7, toplota - vroukina- gor5nie, ognevica - 'egavica; the variability of the word formation: prokaza - proka'enie, gnoi - gnoenie, nemo]6 - nemo]ie - nemo]6stvo, 'ivina - 'ivenica,; through the prefixal word formation: nastoud7; then the suffixal: gnoenie, 'l7t5nica, tr3savica, ognevica; the forming of adjectives from the respective names: isc5litel6n7, ned4'6n7, ned4'6liv7, neoslab6n7, nogobol5znen7, raslablen7, stroupiv7; as well as the participation of these lexemes in the formation of composites: bol5znoro'denie, vr7toglav6stvo, glavobolie, nogobolie, kr7vote=enie, o=obol6, etc. In the standard Macedonian language, a large number of these terms is preserved: болест, гангрена, жолтица, кашлица, краста, лишај, рана, струп, треска, урок, чир, чума etc.